Investigating Critical Thinking Skills and Microlearning Integration in English Learning Material Web-Based of Eighth Graders - Rizka Patrika Rizal; Ifan Iskandar; Siti Drivoka Sulistyaningrum (Scope : Journal of English Language Teaching, 2023)
Microlearning has been widely popular in English language learning. It has some potentials; critical thinking, lowering cognitive load, focusing on learning, and bridging the theory-practice gap in the 21st century learning. This research aims to investigate how critical thinking skills and microlearning-based model are integrated in the English learning material web-based of eighth graders. Qualitative content analysis was utilized as the method for this research. An English learning material web-based was analyzed by using critical thinking skills descriptors from and microlearning descriptors. The findings reveal that the English learning material web-based consists of 7 out of 11 descriptors of critical thinking and includes of 6 out of 9 microlearning descriptors. However, it is indicated that the English learning material web-based of eighth graders are not fully incorporated with the critical thinking skills and microlearning-based model.